Expanding the phenotype of phosphomannomutase-2 gene congenital disorder of glycosylation: Cervical dystonia - Rossi, Malco Damián (2017)
Dear EditorPhosphomannomutase-2 deficiency-congenital disorder of glycosylation (PMM2-CDG), congenital disorder of glycosylation type-Ia or Jaeken syndrome (MIM #601785) is an autosomal recessive inherited condition of abnormal glycosylation of N-linked oligosaccharides [1]. Disease course is variable, ranging from infantile forms with multisystem involvement and a childhood-adult ataxia-intellectual disability type with neurologic stable form [1,2]. The phenotypic spectrum includes morphological abnormalities, ataxia, developmental delay, strabismus, retinopathy, seizures, stroke-like episodes, peripheral neuropathy, hypergonadotropic hypogonadism and thrombotic events [2,3]. Brain imaging displays cerebellar and brainstem atrophy. We describe two sisters with PMM2-CDG that present with cervical dystonia that to our knowledge has not been previously reported.Thirty-three and 30-year-old sisters born to non-consanguineous healthy parents of Spanish-Italian ancestry were studied. There was no other remarkable family history (Fig. 1).Both patients were the product of an uneventful pregnancy with no delivery complications. At 4 months of age, patient III:3 showed a developmental delay. At three years-old, unsteady gait was detected. Strabismus was surgically treated. At the age of five years, action limb incoordination and tremor were recognized and from ten to twenty-one years of age, axial and appendicular ataxia increased. Since then, she began to experience progressive abnormal twisted and sustained posture of the neck with slight jerks. Currently, she is in part-time employment as assistant in a bakery and performs all activities of daily living unaided. On physical examination, she presented slight dysarthria, moderate intellectual disability, slight strabismus, abnormal subcutaneous fat tissue distribution around the hips and upper thighs, kyphoscoliosis, absent deep tendon reflexes in legs and mild limb and gait ataxia. A mild dystonic posture in both hands with dystonic tremor was also present. Slight head rotation and laterocollis to the right, mild retrocollis and dystonic jerks were present (Supplementary video 1). She obtained partial relief by sensory tricks. She denied previous exposure to neuroleptics or other drugs that can induce dystonia.Index patient III:4 showed failure to thrive and developmental delay from approximately three months of age and delayed language and unsteady gait were detected at two years-old. Axial and appendicular ataxia increased over the past ten years. On physical examination, she displayed moderate dysarthria and intellectual disability, large ears, nystagmus and mild limb and gait ataxia. A slight cervical anterior shift on the sagittal plane was observed (Supplementary video 1). No hand dystonia was present.Both patients shared the presence of hypergonadotropic hypogonadism and osteopenia. None had multisystemic affectation, seizures, retinopathy, stroke-like episodes, thromboembolic events or inverted nipples.Patient III:3 received clonazepam at 0.5 mg daily, which reduced significantly dystonic tremor in both hands. Trihexyphenidyl and levodopa (up to 1000 mg/day) were tried for six months without improvement of dystonia. Onabotulinum toxin A injections were applied to patient III:3 in seven occasions with partial but acceptable alleviation of cervical dystonia. Total Toronto Western Spasmodic Torticollis Rating Scale scores improved from 23 (worst) to 11 (best) points in the last and most effective application. Treatment in patient III:4 was not necessary due to minor affectation.Liver and renal function, antithrombin III levels, prothrombin time and immunoglobulin-A and G levels were normal in both patients. Brain MRI in patient III:3 revealed marked cerebellar and brainstem atrophy (Fig. 2).